Conservation and prioritization of indigenous vegetables in the Philippines - Oraye, C.D.; Chavez, H.D. de; Aguilar, C.H.M.; Makiling, F.C.; Ladia, V.A. Jr; Enicola, E.E; Maghirang, R.G; Anunciado, M.S; Monville-Oro, Emilita; Gonsalves, Julian Francis; Hunter, D.; Borelli, T; et al. (2023)
Nutrition-related problems are a widespread challenge in the Philippines. Many factors contribute to these problems - the availability and affordability of vegetables, for example, which are jeopardized by challenges such as seasonality and inconsistent yields due to the impacts of climate change. Crop improvement and on-farm diversification, particularly using indigenous vegetables (IVs), can help address these challenges, while also improving rural livelihoods, nutrition, and food security; and even safeguarding local culture and tradition.